Pop-Up Book Interactive Media to Improve Student Learning Outcomes in Science Subjects, Hindu-Buddhist Kingdom Material, Grade IV Elementary School - Ariyani, Ika Rizqi; Setiawan, Deni (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2025)
Natural Science (IPA) learning at the Elementary School level often faces challenges in terms of student engagement and understanding of the material, especially when the material has abstract or historical characteristics such as the topic of the Hindu-Buddhist Kingdom. Many students have difficulty in understanding narrative and historical concepts when delivered conventionally through lectures or less interesting textbooks. This research is an R&D research. This R&D research refers to the Borg and Gall model which aims to develop and test the feasibility and effectiveness of Pop-Up Book Interactive Media. The population in this study consisted of 5 small-scale test subjects from grade IV of SD Negeri and 20 large-scale test subjects from class IV of SD Negeri 04. The results of this study lead to the conclusion that the interactive pop-up book containing material on Hindu-Buddhist Kingdoms in Indonesia for Class IV of SD Negeri 04 Krajankulon, Kendal Regency is feasible and effective in facilitating student learning.The implications of this study indicate that the use of interactive mediapop-up bookcan be an effective alternative in improving student learning outcomes, especially in science materials related to historical topics such as the Hindu-Buddhist Kingdom. The results of this study can encourage teachers to be more creative in choosing and developing interesting learning media that are in accordance with the characteristics of elementary school students.